Development and application of a clinical core data set for deep brain stimulation in Parkinson’s disease, dystonia or tremor: from data collection to data exchange and data sharing - Anna-Lena Hofmann; Jonas Widmann; Lilly Brandstetter; Udo Selig; Fabian Haug; Julian Haug; Rüdiger Pryss; Jasper Mecklenburg; Andrea Kreichgauer; Philipp Capetian; Christian J. Hartmann; Christian Niklas; et al. (Neurological Research and Practice)
Abstract Background Comprehensive clinical data regarding factors influencing the individual disease course of patients with movement disorders treated with deep brain stimulation might help to better understand disease progression and to develop individualized treatment approaches. Methods The clinical core data set was developed by a multidisciplinary working group within the German transregional collaborative research network ReTune. The development followed standardized methodology comprising review of available evidence, a consensus process and performance of the first phase of the study. To ensure high data quality, measures for standardized training, monitoring as well as plausibility and data quality tests were implemented. Results The clinical core data set comprises information about medical history, clinical symptoms, information about deep brain stimulation surgery, complications and outcome for the main neurological movement disorders Parkinson’s disease, tremor, and dystonia. Its applicability as well as data exchange and quality control was tested within the first phase of the study in 51 patients from Würzburg. Conclusions Within the ReTune project, a standardised clinical core data set for Parkinson’s disease, dystonia and tremor was developed. The collection as well as concepts for the implementation of monitoring and data exchange were elaborated and successfully tested. Trial registration number ClinicalTrials.gov (DRKS-ID: DRKS00031878).